Automatic Power Transfer Control System Using Esp 32 Based on Wokwi Simulation - Alamsyah Harahap; Hamdani Hamdani; Ahmad Dani (SEAN Institute, 2026)
The reliability of electrical power systems is crucial for supporting the continuity of critical sector operations. This study aims to design, implement, and evaluate an Automatic Transfer Switch (ATS) system using ESP32 microcontroller through Wokwi simulation platform. The research employs Research and Development (R&D) methodology with ADDIE approach, encompassing analysis, design, development, implementation, and evaluation phases. The system is equipped with intelligent control algorithms including moving average filter with 10-sample window size and multi-criteria fault detection requiring 5 consecutive samples for verification. Testing was conducted through four main scenarios: fault detection, transfer time measurement, return transfer, and system stability evaluation. Results demonstrate that the system achieves excellent performance with average transfer time of 2,391 seconds, significantly faster than IEEE 446-2017 standard (10 seconds). Voltage detection accuracy reaches 98.9% with MAPE of 1.08%, while system stability shows false switching rate of only 1.25%. The switching mechanism is dominated by relay mechanical delay (91.5% of total transfer time), with detection time contributing only 6.5% and processing time 2.0%. Compared to previous studies, ESP32-based ATS offers competitive performance with optimal balance between speed, accuracy, and cost-effectiveness. This research validates the effectiveness of simulation-driven development methodology using Wokwi platform, reducing development time by 65% ​​and prototyping costs by 70%. The findings provide a significant contribution to developing accessible and efficient ATS solutions for small and medium-scale applications, while demonstrating Wokwi's capability as a reliable embedded systems development tool.